HUBUNGAN SIKAP BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMK N 2 MERANGIN - Awatif (Pendidikan Matematika | STKIP YM Bangko, 2022)
Mathematics lessons have always been a frightening thing for most students so that the achievements or learning outcomes achieved are unsatisfactory. This study aims to identify and describe a significant relationship between learning attitudes and students' mathematics learning outcomes. This type of research uses the correlation method. The sampling technique uses Simple Random Sampling. The selected sample was 57 people from 130 people. Data collection techniques through questionnaire sheets student learning attitudes and student learning outcomes. Then the analysis requirements test was obtained, namely the data were normally distributed and the data had a linear pattern, so the data processing used a Significance Test using the Z test formula. Based on calculations using the product moment correlation formula, or 0.783 > 0.297. Furthermore, the learning attitude variable contributed 61.13%. This shows that 61.13% of student learning outcomes relate to learning attitudes and the remaining 38.88% relate to other factors. Furthermore, the Significance test using the Z test formula obtained and , so that or 5.934 > 1.96, Ho is rejected and Ha is accepted, it can be concluded that there is a significant relationship between learning attitudes towards learning outcomes mathematics class XI students of SMK N 2 Merangin